The little black book of innovation : how it works, how to do it - Anthony, Scott D. (Harvard Business Review Press, 2012)
Innovation may be the hottest discipline around today, in business circles and beyond. And for good reason. Innovation transforms companies and markets. It is the key to solving vexing social problems. And it makes or breaks professional careers. For all the enthusiasm the topic inspires, however, the practice of innovation remains stubbornly impenetrable. No longer. In this book the author draws on stories from his research and field work with companies like Procter & Gamble to demystify innovation. He presents a simple definition of innovation, breaks down the essential differences between types of innovation, and illuminates innovation's vital role in organizational success and personal growth. This unique hybrid of professional memoir and business guidebook also provides a powerful 28-day program for mastering innovation's key steps: (1) Finding insight, (2) Generating ideas, (3) Building businesses, and (4) Strengthening innovation prowess in workforces and organizations. Using several illustrative case studies and vignettes from a range of companies around the globe, this playbook teaches people how to turn themselves or their companies into true innovation powerhouses.